ROAD UTILISATION RESTRICTION POLICY IN KOPELMA BANDA ACEH, INDONESIA: A STUDY OF THE CONCEPT OF HAQQ AL-MURUR AND LAW NUMBER 38 OF 2004 - Fitriani Mulkan; Maidawati; Hasan Sazali (JURISTA: Jurnal Hukum dan Keadilan, 2024)
This article aims to identify the road restriction policy in Kopelma Darussalam according to the concept of haqq al-murur and Law Number 38 Year 2004. This research uses a qualitative approach with descriptive analysis method, as well as empirical juridical approach to evaluate the implementation of road utilisation restriction policy in the field. The results showed that, the agreement obtained between Syiah Kuala University and UIN Ar-Raniry regarding the use of road access as community mobility agreed to be reopened and utilised together. However, in this case there are still some access hour limits on the closure of these roads such as Jalan Bayeun, Jalan Hamzah Fansuri, then the intersection of three Jalan Tgk. Chik Pante Kulu, North Sector precisely in front of Mushalla Fathun Mubin. However, the implementation of Syiah Kuala University's policy on road utilisation restrictions in Kopelma Darussalam must consider the balance between individual rights to pass with the greater public interest, in accordance with the principle of haqq al-murur and Law Number 38 Year 2004